Equilibrium depth and time scale of local scour around a forced vibrating pipeline - Zhang, Zhimeng (2024)
The equilibrium depth and time scale of the scour evolution of a forced vibrating pipeline in unidirectional currents are experimentally investigated under clear-water conditions (θ < θcr, θcr = critical Shields parameter) with a water depth of 0.2–0.4 m and approach velocity of 0.125–0.261 m/s. The pipeline model with a diameter (D) of 3.5 cm, was vertically oscillated in a sinusoidal motion with varying amplitudes (A0 = 2–6 cm) and frequencies (f0 = 0.1–0.6 Hz). The initial gap (G0) between the lower pipeline surface and the undisturbed seabed was fixed at 1D. Both the equilibrium depth and the developing rate of the scour hole increase with the vibration amplitude, frequency, and the Shields parameter ratio (θ/θcr); the influence of A0 on accelerating the scour rate is more significant at high-amplitude conditions (A0 > G0) due to the direct impact of the pipe on the sand bed when compared with the low-amplitude conditions (A0 < G0). The scour time scale increases with the increase of the maximum pipe oscillation velocity and the Shields parameter ratio. A new empirical formula in exponential form for predicting the scour development history is proposed by considering the pipeline vibration effect through three different coefficients – vibration factor αe, coefficient Ce, and exponent ne. Both αe and Ce increase as the maximum pipe oscillation velocity increases. On the other hand, ne decreases with the increase of A0 and f0, where ne is mainly influenced by the vibration frequency in the low-amplitude condition, with vibration frequency only exerting a limited impact on ne in the high-amplitude condition.